KURIKULUM PENDIDIKAN ISLAM PERSPEKTIF IMAM AHMAD BIN HANBAL - Pahrurroji (Qiro'ah : Jurnal Pendidikan Agama Islam, 2024)
This research examines the Islamic education curriculum from the perspective of Imam Ahmad bin Hanbal. Against the background of the dualistic nature of education in Indonesia, this research aims to explore and explain the concepts of Islamic education that have been put forward by Imam Ahmad bin Hanbal. This research uses a qualitative method with a descriptive-analytical approach to the works of Imam Ahmad bin Hanbal as well as a study of related literature, such as "Musnad Ahmad bin Hanbal", "Kitab as-Sunnah", and others. The research results show that the educational curriculum taught by Imam Ahmad emphasizes the integration of religious knowledge and world science, as well as the importance of morals and ethics in education. It is hoped that these findings can make a positive contribution to the development and refinement of a more holistic and integrated Islamic education system in Indonesia.